Differential Behavioral Responses of Solenopsis invicta (Hymenoptera: Formicidae) Workers Toward Nestmate and Non-Nestmate Corpses. Issue 4 (29th July 2020) - Qiu, Hua-Long; Qin, Chang-Sheng; Fox, Eduardo G P; Wang, De-Sen; He, Yu-Rong
Abstract: The removal of corpses (aka 'necrophoric behavior') is critical to sanitation in ant colonies. However, little is known about differences in the necrophoric responses of Solenopsis invicta workers towards corpses of nestmates and non-nestmates. We introduced corpses of S. invicta workers from either intracolony (i.e., nestmate) or intercolony (i.e., non-nestmate) origin at the entrance of artificial nests, and recorded workers' aggressive responses and necrophoric behaviors for analysis. Solenopsis invicta workers displayed distinct responses towards corpses of different origins. Specifically, resident workers were more likely to remove fresh non-nestmate corpses than nestmate corpses, but there was no difference regarding corpses that had been dead for 15 min or longer. Resident workers reacted more aggressively to, and removed more quickly, fresh non-nestmate corpses than corpses of their nestmates. On the other hand, there was no significant difference in the removal time between nestmate and non-nestmate corpses that had been dead for 15 min or longer. Resident workers always displayed stronger aggressiveness towards non-nestmate corpses than nestmate corpses, excepting to corpses that had been dead for 6 h, which elicited a response. No significant correlation between the removal times and aggressiveness levels were detected in any treatments. It remains to be tested whether this differential response is adaptive in how it influences colony fitness and competition.